REFORMASI HUKUM PIDANA: SUATU KAJIAN YURIDIS TERHADAP PEMBUKTIAN TINDAK PIDANA SANTET DALAM KUHP BARU - Sanathana Ishwara, Ade Sathya (IBLAM LAW REVIEW, 2023)
The purpose of this study is to clarify the concept of witchcraft crimes in Indonesia's positive law and the method of proving witchcraft crimes in Indonesia's criminal law reform. The research method used in this study is the normative legal research method, which is derived from the legal literature and is also referred to as doctrinal legal research. Examining the problem of witchcraft means examining a deeper legal issue: how the criminal law policy regarding the criminal act of witchcraft proves that witchcraft is a supernatural act. A formal and rational legal system only tries to capture external actions that can be known empirically and their cause-and-effect relationships proven. In the provisions of the Old Criminal Code in Indonesia, the criminalization of acts of black magic can be seen in Articles 545 to 547. Subsequently, there was a criminal law reform where the regulation of black magic offenses was located in Article 252, the proof of which was only based on the confession of the perpetrator of a criminal act who used supernatural powers. It is predicted that the application of the black magic offense will not be effective in the criminal justice process because it needs to be seen from the perspective of the effectiveness of the legal substance, where the evidence must be reasonable (logical) and acceptable to the five senses in order to find a bright spot in the commission of the black magic crime.